Correlações entre características morfogênicas e estruturais em pastos de capim-braquiária - Santos, Manoel Eduardo Rozalino (2012)
The analysis of both morphogenetic and structural characteristics of pasture allows us to understand the response patterns of the plant to the environment. Thus, this study was conducted to evaluate the associations between the morphogenetic and structural characteristics of Brachiaria decumbens under continuous grazing by cattle. The development of individual tillers in pastures was evaluated under two grazing management strategies during three seasons (winter, spring and summer). Pearson correlations between variables were estimated. The lengths of leaf and stem, number of tillers and leaves per tiller, rates of leaf appearance and elongation of leaf and stem of B. decumbens were positively correlated. There was a negative relationship between appearance and lifespan of leaves (r = -0.89). However, positive correlations between leaf appearance rate and number of tillers (r = 0.64) and between length of stem and leaf senescence rate (r = 0.63) were determined. The B. decumbens modifies its morphogenesis to better adapt to climate and grazing management.